Ancient Portrait Busts of Marcus Aurelius in the National Museum in Poznań - Mroczek, Diana (Études et Travaux, 2021)
The article addresses the collection of Roman portrait busts in the National Museum in Poznań, Poland. The paper focuses on three busts attributed to Marcus Aurelius as an example of durable adaptations and modifications of the originals. It aims to explain frequent misconceptions and interpretations of the sculptures by exploring history and conservation practices.